Determinants and Indicators of competitiveness in the South African suger industry - Nyanzunda, Tafadzwa (My University, 2012)
Regardless of the comparative production efficiencies, the South African sugar industry finds it difficult to export profitably to the global market. This is because the global sugar price is severely eroded by subsidy-induced overproduction in some major sugar-producing countries, such as Brazil. Access to the major markets for raw and refined sugar is furthermore restricted by high tariffs and preferential trade arrangements in the form of tariff rate quotas on major global markets such as Europe. The main objective of this study was to establish the determinants and indicators of the competitiveness of the sugar industry. The data used in the study was industry data obtained from the South African Sugar Association (SASA) in the form of production data, which included area under production, yields, sucrose levels, employment and rainfall. The milling data included the milling capacity, sugar production, employment and the split between raw and refined sugar produced. Due to no responses to the questionnaire, some in-depth interviews were done with the officials from SASA to obtain views of executives in the industry. The data analysed has shown that profitability and growth are consistent indicators of competitiveness. Where profitability was high, growth and productivity were also high. The data analysis showed that positive relationships do exist between production factors and demand conditions. The determinants of competitiveness in the sugar industry were found to be favourable production factors, high rainfall and irrigation, access to markets, downstream processing and government interventions aimed at increasing productivity. The research concluded that advances in technology to increase access to high return markets are indeed a key determinant of competitiveness and that government intervention through increased productivity is also key, to improved competitiveness. The trends in sugar cane production have all been negative, which has largely been linked to the lack of positive markets for sugarcane in the international arena, as well as a lack of clear policy with regards to bio-fuels or a renewable energy strategy.